Varietal Change: The Main Adoption of Technology in Spanish Citrus Culture - Maria Angeles Fernandez-Zamudio; Hayet Kerras; Pedro Caballero; Maria Dolores de-Miguel (Current Research Progress in Agricultural Sciences Vol. 6, 2024)
This study explores how varietal changes have become the primary technological advancement in Spanish citrus farming, serving not only as a crucial factor for optimizing production but also as a response to shifts in consumer demand. Accordingly, the objective has been to assess how varietal change is unfolding over time and its consequences. Methodologically, a series of historical data has been reviewed to explain the evolution of the citrus sector (in terms of area, production, trade, etc.), supplemented by expert interviews to identify the factors influencing the performance of different varieties. Growers select varieties based on expected pricing, commercial and agronomic characteristics, and quality. The market longevity of each variety depends on its performance and the presence of more competitive options. In Spain, certain citrus varieties dominate, with navel oranges—particularly “Navelina” and “Lanelate”—accounting for 37.76% of production, alongside the important late-season white oranges. The mandarin segment is centered on clementines and hybrids, while lemons form another key sector. The sweet orange sector frequently undergoes renewal, primarily within the navel and late-white categories. The findings indicate that early-season clementine varieties often have short market lifespans due to oversupply, whereas mandarin hybrids show significant growth potential driven by rising supermarket demand. The study also considers the impact of varietal clubs that regulate production zones and impose rigorous cultivation and marketing standards, thereby influencing current varietal trends. In conclusion, this research highlights how varietal innovation enhances competitiveness and contributes to the sustainability of Spanish citrus farming amid evolving market pressures.